Building performance - Ali Mehsin al khafajy; Asma mohammed Hussain; Audaay Abbas Abood (Iraqi Journal of Architecture and Planning, 2018)
The performance concept expressed as the distance between what is needed and what is realized, and asolution to the problem of evaluating the suitability of the product for the application, which in turn is animportant factor from which to evaluate the building and therefore the identification and development paths ofpractice and professional experience in the housing field . the performance concept adopted after the needdictated by the new circumstances in the construction field as a result of the emergence of new concepts aimwas to move away from compliance to traditional construction systems and the transfer rate from site to thefactory .an experience of prefabrication can be solution to a growing problem of housing reliance on the massproduction and the provision at the time of implementation as well as the economy and resources, these processof manufacturing - often - at the expense of performance dimension for the user and his need to shelter .Through a review of performance studies and prefabricated structural systems studies. the researchpointed :â€ the absence of a clear vision of the performance concept and its impacts on residential buildingsprefabricated and the absence of mechanism for evaluate it â€œ to be the research problem .The aim of the research is determined to : â€œ provide a vision of the performance concept and itsimpacts on residential buildings prefabricated and re-evaluation of these buildings in accordance with theperformance concept â€œ. To achieve his aim , the research separate the procedural theory aspects of theoperational aspects without losing sight of the integration of both theoretical and practical dimension to theperformance concept . In this context, research split into two ; the first terms definition the performance conceptand related aspects and its dimensions up to the extraction a conceptual framework for the basic concept Thesecond terms addressed the field study the adoption of Al-Salam neighborhood in Baghdad as a case study andresearch was (50) random sample of residents of this district to evaluate the residential buildings performance,which made it possible to visualize residential complex performance (under study) in general .